Paul Feyerabend’s Amodern philosophy - Mączka, Dorian (Hybris, 2018)
Paul Feyerabend’s philosophy, mainly due to his radically pluralistic claims, may be regarded as an example of postmodern philosophy of science. At the same time Feyerabend’s thought contains some strictly modern ideas and noticing those ideas is important for proper reading of his works. In this paper, in order to properly understand this conceptual tension, I compare Feyerabend’s philosophy with Bruno Latour’s idea of amodernity. The first part of the paper presents modern and postmodern themes present in Feyerabend’s works. The second part elucidates the concept of amodernity expounded by Latour in the essay We have never been modern. In the third part I show that Feyerabend’s philosophy displays all of the most important features of amodern way of thinking (in Latour’s sense). In the final section I discuss how the interpretation of Feyerabend’s thought as an example of amodern philosophy may be fruitful in further research.